Speaking of the Genre Types of USA Institutional Political Discourse - A. A. Alimdjanov; T. P. Tretyakova (Дискурс, 2020)
Introduction. Institutional government discourse can be analyzed in the framework of a dialogical scheme in which actors (politicians and the press) as well as parameters such as time and place play an important role in the formation of genre characteristics. Genre types of institutional discourse are open systems in which the process of stereotyping allows the identification of different forms of belief. The purpose of this paper is to define genre types as a priority format for communicative interaction between its main participants such as politicians and the press.Methodology and sources. The types of dialogic genres of contemporary American political discourse are analyzed within the framework of a dialogical scheme in which the participants in communication involved in the regulated format of communication in the struggle for power observe all external extralinguistic forms of communication. Despite the rapid development of such an innovative factor as Internet communication, the genre specificity of American political discourse remains quite rigidly structured.The material for the study was the socalled "frozen" sites of the three last US presidents before D. Trump (B. Clinton, G. Bush, and B. Obama) and the current site of D. Trump, which reflected "genres" The White House. For the analysis, dialogical formats were identified that allow us to identify the correlation of interactive characteristics of the political dialogue Results and discussion. Dialogue genres can be divided into four large classes, taking into account the status and number of interlocutors: 1) any event with the participation of accessible media, where the right to disseminate information is provided to all media (press availability);2) interviews, where the right to receive and disseminate information provided exclusively to the interviewing organization (interview); 3) an audience meeting with a politician (town hall meeting), a politician communicates with a certain group of people through the media; 4) debates.Conclusion. The analyzed material allows us to establish that the format of the genre types of dialogical communication is strictly adhered to and that they are resistant to changes, despite the existing dynamic processes taking place in digital communication. In this regard, American political discourse is quite conservative and stable.